2012
DOI: 10.1093/jopart/mus010
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofit Sector Growth and Density: Testing Theories of Government Support

Abstract: Theories of nonprofit density have assumed a variety of dispositions toward the state, including opposition, suspicion, indifference, and mutual dependence. In this article, we conduct the first large-scale simultaneous empirical test of the two most prominent nonprofit theories: government failure theory and interdependence theory. The former characterizes nonprofit activities as substitute or oppositional to state programs, accounting for the limitations and failures of government-provided services and more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
193
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(208 citation statements)
references
References 50 publications
6
193
1
8
Order By: Relevance
“…Such behavior is similar to that articulated by Mosley (2012), in which social service providers advocate with government funders to ensure direct public financing for charities continues over time. In fact, several studies have found that government funding of charitable nonprofits leads to greater geographical concentration and/or survival of such organizations (Hager, Galaskiewicz, & Larson, 2004;Lecy & Van Slyke, 2013;Luksetich, 2008;Matsunaga &Yamauchi, 2004;Twombly, 2003).…”
Section: Nonprofit Charities Tax Exemptions and Rent-seekingmentioning
confidence: 99%
“…Such behavior is similar to that articulated by Mosley (2012), in which social service providers advocate with government funders to ensure direct public financing for charities continues over time. In fact, several studies have found that government funding of charitable nonprofits leads to greater geographical concentration and/or survival of such organizations (Hager, Galaskiewicz, & Larson, 2004;Lecy & Van Slyke, 2013;Luksetich, 2008;Matsunaga &Yamauchi, 2004;Twombly, 2003).…”
Section: Nonprofit Charities Tax Exemptions and Rent-seekingmentioning
confidence: 99%
“…Governments benefits from stable relationships with nonprofits because risk is managed, goods are produced, services delivered, and the costs of rebidding contracts or awarding grants to new and potentially unknown recipients are lowered (2016) [21]. Therefore the social organization as the accepting side is the important parts in the process of government purchasing public services.…”
Section: In the Early The Level Of Local Economic Development Is Thementioning
confidence: 99%
“…Harrison and Thornton (2014) point out that, due to the rate of nonprofit proliferation, the nonprofit sector is increasingly dense; there are more nonprofits per capita today than in the past. We know that proliferation is in part caused by free market entry (RoseAckerman 1982), increased government funding (Lecy and Van Slyke 2013), and the high survival rates of nonprofits (Harrison and Laincz 2008).…”
Section: Crowding and Financial Resources In The Nonprofit Sectormentioning
confidence: 99%